2004
DOI: 10.1089/tmj.2004.10.s-81
|View full text |Cite
|
Sign up to set email alerts
|

Prison Telemedicine and Telehealth Utilization in the United States: State and Federal Perceptions of Benefits and Barriers

Abstract: Although national justice and technology associations have endorsed the utilization of telemedicine and telehealth, little is known about the current utilization of this technology across our nation's correctional facilities. Several voluntary registries and state Web sites exist, but only limited information on telemedicine utilization may be gleaned from these. The purpose of the present study was to fill this void by reporting the utilization patterns in telemedicine programs in state and federal correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…[29][30][31] In the USA, for instance, use of telemedicine started in July 1997 with pulmonary, orthopaedics, diabetic, and dermatology offerings, and currently telemedicine is a key part of an integrated and successful health care system for inmates. [31][32][33][34][35][36] In Europe this should be recommended, as problems of health and shortage of resources in prisons were described on the last report of the European Prison Observatory. [37] To review and monitor the benefits of telemedicine at national and regional level, the World Health Organization (WHO) established the Global Observatory for e Health (GOe).…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] In the USA, for instance, use of telemedicine started in July 1997 with pulmonary, orthopaedics, diabetic, and dermatology offerings, and currently telemedicine is a key part of an integrated and successful health care system for inmates. [31][32][33][34][35][36] In Europe this should be recommended, as problems of health and shortage of resources in prisons were described on the last report of the European Prison Observatory. [37] To review and monitor the benefits of telemedicine at national and regional level, the World Health Organization (WHO) established the Global Observatory for e Health (GOe).…”
Section: Introductionmentioning
confidence: 99%
“…24 Thus, the unprecedented accessibility that patients have to mobile phones today, and the ubiquity of the cellular network, provide the potential to greatly alleviate the cost pressures in health-care management.…”
Section: Applying the Visor Business Model Value Propositionmentioning
confidence: 99%
“…Not surprisingly, the treatment of high-risk heart failure patients accounts for an estimated 1%-2% of the total heart care budget both in Europe and the US. 24 Studies have shown that with telemonitoring, survival rates have improved, and there has been about a 26% reduction in number of days of in-hospital stays for patients. [28][29][30] This is a viable technology, as shown by the large number of internet-based wireless telemedicine applications, such as portable health monitoring devices and mHealth units, which seamless connect wirelessly with a central service center.…”
Section: Pereiramentioning
confidence: 99%
“…Currently there is a growing body of evidence regarding the effectiveness of video-and audio-based interventions for a variety of acute and chronic conditions seen in primary care, such as diabetes, asthma, heart failure, and hypertension. 5,6,[8][9][10][11][12][25][26][27][28][29][30][31]34,[36][37][38] Typically these include conditions for which there is a reasonable level of certainty in establishing a diagnosis and generating a treatment plan, especially when visual information coupled with access to a medical record with diagnostic studies and imaging is available. 5,19,30 In general, conditions that are not suitable for telemedicine are those for which an in-person visit is required to evaluate the patient because of the severity of presenting symptoms, the necessity of haptic information, the need for protocol-driven procedures, or the need for aggressive interventions.…”
Section: Practice Guidelinesmentioning
confidence: 99%
“…The literature contains examples of clinical effectiveness of successful telemedicine programs in a variety of settings, including patient homes, childcare centers, schools, chronic care facilities, the workplace, and prisons. 6,26,27,33,36,37,41 All legal and regulatory requirements and ethical considerations shall be used in these settings.…”
Section: B Geriatricmentioning
confidence: 99%